Comparative analysis of selected methods of carbapenemase determination among clinical Klebsiella pneumoniae - Agata Pruss; Alicja Skierska; Paweł Kwiatkowski; Helena Masiuk; Joanna Jursa-Kulesza; Stefania Giedrys-Kalemba; Iwona Bilska; Monika Sienkiewicz; Maria V. Melnyk; Barbara Dołęgowska (PLoS ONE, 2025)
Klebsiella pneumoniae is a typical opportunistic pathogen that exhibits multiple virulence factors and antibiotic resistance conditioning mechanisms. Carbapenemases are enzymes that help bacteria to exhibit the strongest resistance against antibiotics. Therefore, in routine microbiological diagnoses, it is crucial to confirm antibiotic-resistant strains, including carbapenemase-producing bacteria strains, isolated from patients. Two types of tests play an important role here: phenotypicand molecular diagnostic methods. The latter complement phenotypic tests and a mandatory procedure to confirm the detection of carbapenemases. This study aimed to evaluate the usefulness and effectiveness of tests and methods used to identify and confirm the ability of clinical K. pneumoniae strains to produce carbapenemases. The production of carbapenemases was assessed using phenotypic and genetic methods. The strains tested showed complete resistance to most beta-lactams and varying sensitivity to drugs from the quinolone carbapenem group and aminoglycosides. Among the most commonly produced carbapenemases were the metallo-beta-lactamase (NDM) family. The most accurate phenotypic method for detecting carbapenemases was the NG CARBA-5 assay, and the PCR method confirmed these results. Notably, a few inconclusive results were obtained for NDM-positive and VIM-positive strains when the disk diffusion method and CIM test were used. Further, the Carba tube assay and the RAPIDEC CARBA NP assay produced questionable results for the OXA-48 strain group. This group also generated false-negative results on Carba’s CHROM ID medium.